2016
DOI: 10.1002/mrm.26348
|View full text |Cite
|
Sign up to set email alerts
|

Multislice CEST MRI improves the spatial assessment of tumor pH

Abstract: Purpose Multislice maps of extracellular pH (pHe) are needed to interrogate the heterogeneities of tumors and normal organs. To address this need, we have developed a multislice acidoCEST MRI acquisition method with a CEST spectrum fitting method that measures in vivo pHe over a range of 6.3 to 7.4. Methods The Phase Offset MultiPlanar (POMP) method was adapted for CEST-FISP MRI to acquire multiple image slices with a single CEST saturation pulse. The Bloch-McConnell equations were modified to include pH bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Last, the extent to which raising pH e would lead to a better intracellular distribution of chemotherapeutic agents in cancer needs to be confirmed. That said, emerging modern technologies, especially several newer in vivo pH-monitoring techniques (6,22,114,123), are expected to greatly facilitate research in this field to unveil novel information to address the existing questions.…”
Section: Some Remaining Questionsmentioning
confidence: 99%
“…Last, the extent to which raising pH e would lead to a better intracellular distribution of chemotherapeutic agents in cancer needs to be confirmed. That said, emerging modern technologies, especially several newer in vivo pH-monitoring techniques (6,22,114,123), are expected to greatly facilitate research in this field to unveil novel information to address the existing questions.…”
Section: Some Remaining Questionsmentioning
confidence: 99%
“…AcidoCEST MRI has been used to measure extracellular pH in tumor models of lymphoma, breast, ovarian, pancreatic, and lung cancer . These studies have shown that tumor extracellular pH is lower in faster‐growing tumors, and increases in early response to drug treatments, demonstrating that acidoCEST MRI is sensitive to the level of tumor metabolism.…”
Section: Acidocest Mrimentioning
confidence: 99%
“…AcidoCEST MRI results were fit using previously published methods (11,23,24,(26)(27)(28). We first averaged the four preinjection images at each saturation frequency.…”
Section: Mri Analysesmentioning
confidence: 99%